EXPERIENCE OF THE REMOTE COURSE IMPLEMENTATION FOR THE ORGANIZATION OF THE INDEPENDENT WORK OF STUDENTS FROM MATHEMATICAL ANALYSIS - Botuzova, Ю.В. (Journal of Information Technologies in Education (ITE), 2017)
The article raises the problem of organization independent work of students. In particular, the model of integration of traditional and distance learning in the form of a blended learning is considered. The experience of introducing a distance course in the discipline "Mathematical Analysis" is described. The purpose of this distance course is the effective organization of independent out of class work of future mathematics teachers. In this paper, the structure of educational and methodological support of the educational process on mathematical analysis is examined, as well as its model in a blended learning is presented. The didactic capabilities of distance technologies are analyzed. The step-by-step scheme of organization of independent work of students in the context of the use of distance course is offered. The scheme consists of the following stages: preparatory, theoretical, practical-activity, controlling, corrective. The author describes in detail the contents of the work of the teacher and students at each of these stages. The peculiarities of planning, developing and implementing a distance course, and the leadership of independent work of students are revealed. For this, the teacher performs the following functions: the formation of a permanent positive student motivation; defining and setting goals and objectives; organization of interaction between students; control and counseling of students in the learning process. A number of psychological and pedagogical problems are highlighted in the implementation of the distance learning form and the ways of their partial or complete elimination are indicated.